Examining the synergetic impact of ability-motivation-opportunity-enhancing high performance work practices. Issue 3 (27th May 2021) - Nadeem, Sadia; Rahat, Hamnah
ABSTRACT: This study examines the impact of ability-motivation-opportunity (AMO) enhancing bundles and their interactions on employee outcomes and perceived organizational performance (POP) using signaling theory. It also examines employee outcomes as mediators, and trust and work autonomy as moderators in these relationships. Based on data from HR managers and 3, 460 employees from 222 organizations, the study presents a 2-1-2 multilevel moderated-mediation model. Results indicate that the motivation-enhancing bundle had a positive impact on POP, and this bundle and its interaction with the ability-enhancing bundle had a negative impact on job satisfaction. The opportunity-enhancing bundle and its interaction with the other two bundles had a positive impact on job satisfaction. Work autonomy and trust acted as moderators in relationships between the bundles, their interactions, and the outcomes.